Salinity Levels on Survival Rate and Development of Mud Crab (Scylla olivacea) from Zoea to Megalopa and from Megalopa to Crab Stage - Pattanee Jantrarotai; Krailerk Taweechuer; Suparp Pripanapong (Agriculture and Natural Resources, 2002)
Effect of salinity on survival rate and development of mud crab (Scylla olivacea) were conducted into two phases: phase I from zoea 1 to megalopa and phase II from megalopa to the crab stage. In phase I, four different levels of salinity, 28, 30, 32 and 34 parts per thousand (ppt) were used. The results showed that zoea reared at 28, 30, 32 and 34 ppt developed to megalopa stage with survival rates of 13.16, 22.19, 8.25 and 7.08 percent respectively. At 30 ppt, zoea developed to megalopa stage with better survival rate than at the other salinity levels (P<0.05). In all salinity levels, high mortality rate of zoea occured during the development of zoea 1 to zoea 3 and was higher than that of zoea developed from stage 3 to megalopa. Duration for development of zoea 1 to megalopa at all salinity levels were 23.64-24.22 days which were not significantly different (P>0.05) among treatments. In phase II, the effect of salinity on survival rate and developmental period of megalopa to the fifth crab stage (C5) at salinity levels of 12, 16, 20, 32, 36 and 40 ppt were studied. The results showed that survival rates of the crab developed from megalopa at 16, 20, 32 ppt were 80.95, 76.19, and 80.95 percent respectively. These figures were significantly higher (P<0.05) than those at 12, 36, and 40 ppt. Time used for megalopa to develop into the fifth crab stage (C5) was influenced by salinity. The developmental period to the fifth crab stage from megalopa were 29.14, 28.25, 30.10, 31.75, 32.55, and 43.50 days, respectively. Aging also had influenced on time for crab development. The more advanced crab stage, the longer time used for the development of crab to the next stage.